Turbulence Formation due to Vortices Interaction in the Laminar Channel Flow behind the Rib - A.B. Mazo; D.I. Okhotnikov (Учёные записки Казанского университета: Серия Физико-математические науки, 2015)
This paper is devoted to the study of local laminar-turbulent transition mechanisms in the channel flow behind the semi-circular rib. Using direct numerical simulation, it was demonstrated that the transition occurs mainly due to the interaction of paired helical vortices at the side walls of the channel behind the rib. If the transverse size of these vortices reaches half of the channel width, their contact causes periodic generation and separation of smaller vortex structures. The latter leads to the local laminar-turbulent transition in the interaction region behind the rib. If the channel width is large enough, the flow stays laminar. The influence exercised by the channel width on the laminar-turbulent transition was studied at a range of Reynolds numbers from 1500 to 3000.